Dreeben-Irimia's introduction to physical therapy practice for physical therapist assistants - Christina M. Barrett; Olga Dreeben-Irimia (Burlington, MA : Jones & Bartlett Learning, 2021)
"Dreeben-Irimia's Introduction to Physical Therapy Practice for Physical Therapist Assistants introduces students to the role of the physical therapist assistant in physical therapy care. This text's goal is to present information in a way that students appreciate all that is necessary to learn to become an effective physical therapist assistant. The text begins by introducing the reader to the profession of physical therapy before covering physical therapy evaluation and the major physical therapy practice specialties, the ethical and legal components of practice, and communication, documentation, and research. The text also emphasizes student success, with the first chapter establishing ways for students to succeed in PTA school and the final chapter focused on developing one's career"-- Provided by publisher
Keywords: Physical Therapist Assistants; Physical Therapy Modalities; Physical Therapy Specialty methods